Avaliação energética e econômica da secagem de grãos utilizando secador de coluna com caldeira aquatubular - Oliveira, Vanderley de (2014)
The present paper aimed at assessing the energy and economic parameters of grain drying, using a watertube boiler. Seeking an energy and economic evaluation of grain drying, it was chosen to research the drying of corn grains, using a column dryer double reuse model Comil CM 150 DR and a watertube boiler model CW 40. Studies were accomplished about the concepts and principles of drying; the technical data of the column dryer CM 150 DR; the Boiler Watertube CW 40; the alternative sources of solid fuels and Energy and Economic Analysis of the System. Considering that the main challenge of the appropriate storage of grains is to maintain the physical, chemical and biological properties the grains hold, imediatly after the harvest. The drying operation is an important part of the processing which precedes the storage, and extremely important for this process. The rational use of energy in the drying of agricultural products can contribute to an economy of fuel and obviously, to the reduction of the drying costs. The drying system with watertube boiler, showed the advanges as follows: stability and control of temperature; modulation of air flow; fuel economy; electrical energy economy; possibility of drying any kind of grain; possiblity of drying seeds; elimination of fire hazard. In the economical analysis, it was considered an investment of R$ 350.000,00; the minimum acceptable rate of return (MARR) of 3,5% per year, the net present value (NPV) in the period of 15 years, will be R$ 452.241,54. The internal rate of return (IRR) is 17,89 % per year. The project has presented profitability index (PI) of 1,29 % and rate of return (ROR) of 29 %, considered attractive. The Payback period, considered as the time required to recover the capital invested in the project, is 7 years, therefore staying positive and indicating economical viability.